Prevalence, etiologies and complications of teeth hypomineralization in pediatrics - Amer, Ameera Ibrahim; Alsaadi, Rana Ali; Almajed, Malak Abdullah; Alzhrani, Rana Ahmad; Asiri, Sara Abdullah; Binthabit, Haifa Mohammed; Alazmi, Awadh Owaidh; Alanazi, Abdulelah Abdulrahman; Almutairi, Ayman Saeed; Alharbi, Abrar Zainalabiddin; Kufiyah, Aseel Khalid (International Journal Of Community Medicine And Public Health, 2021)
Dental hypomineralization represents a major problem in childhood health that can cause serious problems and may even affect the permanent dentition. In previous literature review, the term molar incisor hypomineralization (MIH) has been frequently reported among different studies. However, the clinical problems and complications of the condition are not commonly described among studies in the literature, which adds a value to this current study. The present study was a literature review that aimed to discuss the problems of hypomineralization in baby teeth and the reported common problems according to recent studies in the literature. Tooth loss, anesthetic problems within the anterior teeth, hypersensitivity and the presence of underlying inflammation are potential complications that might affect these patients. Moreover, it was also previously reported that the subsurfaces of the affected enamels are usually porous and soft. On other hand, the surfaces of the intact enamels are usually hypermineralized, hard and smooth, owing to the subsequent post-eruptive maturation. Identification of the underlying etiology and risk factors is important for the proper management of these cases. A systemic origin of the disorder was strongly suggested while other environmental and genetic factors had been suggested. Moreover, establishing a proper diagnosis can be hard due to the presence of some similar disorders. Therefore, a differential diagnosis should be established as it is discussed in this literature.